Autophagy across tissues of aging mice - Julian M. Carosi; Alexis Martin; Leanne K. Hein; Sofia Hassiotis; Kathryn J. Hattersley; Bradley J. Turner; Celia Fourrier; Julien Bensalem; Timothy J. Sargeant (PLoS ONE, 2025)
Autophagy is a ‘waste-disposal’ pathway that protects against age-related pathology. It is widely accepted that autophagy declines with age, yet the role that sex and diet-related obesity play during aging remain unknown. Here, we present the most comprehensive in vivo study of autophagic flux to date. We employed transgenic mice overexpressing tandem-florescent LC3B (RFP-GFP-LC3B) to measure autophagic flux in the blood (PBMCs), heart, and motor cortex neurons of aging mice that were fed regular chow or a high-fat diet for 6-, 12- or 18-months. In male mice, aging decreased autophagic flux in the heart, increased it in the blood, and had no effect in motor cortex neurons. Age-dependent changes autophagic flux were less pronounced in female mice. High-fat diet influenced autophagic flux in the blood and heart of male but not female mice. Overall, we uncovered sexual dimorphisms that underpin how autophagy changes with age across different tissues and in response to a high-fat diet.